The Search for a Subtype-Selective PET Imaging Agent for the GABAA Receptor Complex: Evaluation of the Radiotracer [11C]ADO in Nonhuman Primates. (15th September 2017) - Lin, Shu-fei; Bois, Frederic; Holden, Daniel; Nabulsi, Nabeel; Pracitto, Richard; Gao, Hong; Kapinos, Michael; Teng, Jo-ku; Shirali, Anupama; Ropchan, Jim; Carson, Richard E.; Elmore, Charles S.; et al.
The myriad physiological functions of γ-amino butyric acid (GABA) are mediated by the GABA-benzodiazepine receptor complex comprising of the GABAA, GABAB, and GABAC groups. The various GABAA subunits with region-specific distributions in the brain subserve different functional and physiological roles. For example, the sedative and anticonvulsive effects of classical benzodiazepines are attributed to the α1 subunit, and the α2 and α3 subunits mediate the anxiolytic effect. To optimize pharmacotherapies with improved efficacy and devoid of undesirable side effects for the treatment of anxiety disorders, subtype-selective imaging radiotracers are required to assess target engagement at GABA sites and determine the dose–receptor occupancy relationships. The goal of this work was to characterize, in nonhuman primates, the in vivo binding profile of a novel positron emission tomography (PET) radiotracer, [ 11 C]ADO, which has been indicated to have functional selectivity for the GABAA α2 /α3 subunits. High specific activity [ 11 C]ADO was administrated to 3 rhesus monkeys, and PET scans of 120-minute duration were performed on the Focus-220 scanner. In the blood, [ 11 C]ADO metabolized at a fairly rapid rate, with ∼36% of the parent tracer remaining at 30 minutes postinjection. Uptake levels of [ 11 C]ADO in the brain were high (peak standardized uptake value of ∼3.0) and consistent with GABAA distribution, with highest activity levels in cortical areas, intermediate levels in cerebellum and thalamus, and lowest uptake in striatal regions and amygdala. Tissue kinetics was fast, with peak uptake in all brain regions within 20 minutes of tracer injection. The one-tissue compartment model provided good fits to regional time–activity curves and reliable measurement of kinetic parameters. The absolute test–retest variability of regional distribution volumes ( V T ) was low, ranging from 4.5% to 8.7%. Pretreatment with flumazenil (a subtype nonselective ligand, 0.2 mg/kg, intravenous [IV], n = 1), Ro15-4513 (an α5 -selective ligand, 0.03 mg/kg, IV, n = 2), and zolpidem (an α1 -selective ligand, 1.7 mg/kg, IV, n = 1) led to blockade of [ 11 C]ADO binding by 96.5%, 52.5%, and 76.5%, respectively, indicating the in vivo binding specificity of the radiotracer. Using the nondisplaceable volume of distribution ( V ND ) determined from the blocking studies, specific binding signals, as measured by values of regional binding potential ( BP ND ), ranged from 0.6 to 4.4, which are comparable to those of [ 11 C]flumazenil. In conclusion, [ 11 C]ADO was demonstrated to be a specific radiotracer for the GABAA receptors with several favorable properties: high brain uptake, fast tissue kinetics, and high levels of specific binding in nonhuman primates. However, subtype selectivity in vivo is not obvious for the radiotracer, and thus, the search for subtype-selective GABAA radiotracers continues.